2017
DOI: 10.1017/s147474721700004x
|View full text |Cite
|
Sign up to set email alerts
|

The financial feasibility of delaying Social Security: evidence from administrative tax data

Abstract: Despite the large and growing returns to deferring Social Security benefits, most individuals claim Social Security before the full retirement age. In this paper, we use a panel of administrative tax data on individuals likely to financially benefit from delaying Social Security claiming to explore the relationship between Social Security claiming and distributions from tax-advantaged retirement savings accounts. We find that the majority of our sample claim Social Security prior to taking distributions from I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Mastrobuoni (2009) focused on the gradual increase of the FRA to examine how this change in benefit generosity impacted the age at retirement, finding that that mean retirement age increased by approximately one-half of the increase in the full retirement age. Using the HRS, Gustman and Steinmeier (2009) also arrive at similar conclusions: the increase in the FRA, increase in the delayed retirement credit and the removal of the earnings test in 2000 served to increase labor force participation for those between the ages of 65 and 67.…”
Section: Previous Literaturementioning
confidence: 58%
See 1 more Smart Citation
“…Mastrobuoni (2009) focused on the gradual increase of the FRA to examine how this change in benefit generosity impacted the age at retirement, finding that that mean retirement age increased by approximately one-half of the increase in the full retirement age. Using the HRS, Gustman and Steinmeier (2009) also arrive at similar conclusions: the increase in the FRA, increase in the delayed retirement credit and the removal of the earnings test in 2000 served to increase labor force participation for those between the ages of 65 and 67.…”
Section: Previous Literaturementioning
confidence: 58%
“…In particular, for most potential SS retirement beneficiaries, there is a substantial financial return to delaying claiming SS benefits and receiving higher benefits later, but most beneficiaries claim benefits immediately upon retiring. To explore whether liquidity constraints -the need to have cash on hand -drive these decisions, Goda et al (2015) use administrative tax data on primary earners from the 1940 birth cohort to analyze SS claiming behavior in concert with distributions from IRAs. Like the studies cited above, they find that a significant proportion of the sample starts claiming at the age of 62.…”
Section: Previous Literaturementioning
confidence: 99%
“…We note, however, thatGoda, Shoven, Ramnath, and Slavov (2015) found that one-third of Social Security early retirees had financial assets in their Individual Retirement Accounts sufficient to finance at least two additional years of deferral, and about one-quarter could self-finance at least four years of deferral. Other assets were not included in that calculation, so that the likely impact of liquidity constraints is probably far lower.10 As noted above, the survey module is detailed inMaurer, Mitchell, Rogalla, and Schimetschek (2016a).…”
mentioning
confidence: 61%
“…Also, the tax regulation on entrepreneurship, and the particularities for people with disabilities (Goda, ramnath, shoven & slavov, 2018;spreat, 2017), together with the organizational aspects become an element that can directly affect the success or failure of the entrepreneur.…”
Section: Introductionmentioning
confidence: 99%